Inside the Swashing Glossolalias of Artaud - Almeida, Gil Roberto; Lignelli (Universidade de Brasília – UnB, Brasília/DF, Brazil), César (Revista Brasileira de Estudos da Presença, 2022)
By analyzing the works of Artaud it is evident a set of ideas that suggests principles for vocality in the context of performance. This vocality is based on a notion of glossolalia as a concept linked to enunciative practices, especially as potency for irrationalizing vocal strata. Thus, glossolalia can add sound-poetic values that destabilize voice related aspects of meaning production and perception. Here we seek a discussion of possible boundaries in vocal production. We will appropriate concepts from the work of Deleuze and Guattari, as well as considerations from Certeau and Pozzo. This article aims to arouse and appreciate aspects of a glossolalic vocality, seeking to expand possibilities for the contemporary performer, problematizing the context of his vocal practices.